ENERGY AND ECONOMIC EFFICIENCY OF BIOETHANOL PRODUCTION DEPENDING ON THE QUALITY OF CORN GRAIN - Vitalii Palamarchuk; Roman Lohosha; Vadim Krychkovskyi (Baltic Journal of Economic Studies)
The present article expounds upon the findings of research conducted on the energy and economic efficiency of bioethanol production, with the quality of corn grain taken as the primary variable. The research was conducted at the experimental field of Vinnitsa National Agrarian University in the conditions of the state enterprise "Kordelivske" of the Institute of Potato Growing of the National Academy of Agrarian Sciences of Ukraine in 2015-2017. The cultivation techniques incorporated elements that are widely accepted for the growing zone, with the exception of the factors under study. The elements of the yield structure, including the productivity of maize hybrids, were determined in accordance with established methods. The harvesting and accounting of the crop was conducted manually at each experimental site, followed by weighing and conversion to standard grain moisture. The yield of bioethanol from grain was calculated as the amount of ethanol obtained from a ton of carbohydrates in terms of starch, i.e., the ethanol yield. The purpose of the article is to assess the energy and economic efficiency of bioethanol production depending on the quality of corn grain. The results of studies of the influence of foliar fertilisation with a bacterial preparation based on beneficial symbiotic and associative microorganisms Biomag, microfertilisers "ROSTOK" corn, Ecolist Mono Zinc, carried out in the phase of 5-7 and 10-12 leaves of corn, on the level of pre-harvest grain moisture, the number of rows of grains are presented, number of grains in a row, weight of 1000 grains, starch content in grain, productivity and bioethanol yield in hybrids of early maturing group Kharkiv 195 MV (FAO 190) and DKS 2971 (FAO 200), medium early group DKS 3795 (FAO 250) and DKS 3871 (FAO 2480) and medium maturing group DK 315 (FAO 310) and DK 440 (FAO 350) in agro-ecological conditions of the Forest-Steppe of Right-Bank Ukraine. The research is grounded in an evaluation of the efficacy of optimising the supply of plant nutrients through foliar fertilisation in the formation of grain yield and quality. Additionally, it explores the potential for grain processing into bioethanol, contingent on the augmentation of grain yield and the attainment of acceptable quality. Corn is the most productive source of purified bioethanol from biomass feedstocks, and the price of 1 ton of bioethanol is higher than that of sugar beet, creating a favourable environment for the production of this type of biofuel. From an economic perspective, bioethanol production from corn is one of the most efficient options for bioethanol production in Ukraine. It has been established that the production of bioethanol from maize grain is an innovative technology: it improves the ecological situation and reduces harmful effects on the human body and the environment. The use of maize as a raw material partially resolves the existing conflict of interest associated with the use of food resources for bioethanol production. In turn, the opening of maize processing plants for bioethanol, with the production of biomethane and organic fertilisers, is a very profitable business.